Hitchcock's Appetites The Corpulent Plots of Desire and Dread - McKittrick, Casey (Bloomsbury Academic, 2016)
In Hitchcock's Appetites, Casey McKittrick offers the first book-length study of the relationship between Hitchcock's body size and his cinema. Whereas most critics and biographers of the great director are content to consign his large figure and larger appetite to colorful anecdotes of his private life, McKittrick argues that our understanding of Hitchcock's films, his creative process, and his artistic mind are incomplete without considering his lived experience as a fat man. Using archival research of his publicity, script collaboration, and personal communications with his producers, in tandem with close textual readings of his films, feminist critique, and theories of embodiment, Hitchcock's Appetites produces a new and compelling profile of Hitchcock's creative life, and a fuller, more nuanced account of his auteurism.
Description based on print version record.
Knowledge Unlatched Round 2
Keywords: Performing Arts / Individual Director (see Also Biography & Autobiography / Entertainment & Performing Arts); Performing arts; Electronic books